Differences in Student Learning Performance in Online Learning: Based on Gender and Field of Science - Albeta, Sri Wilda; Haryati, Sri; Aldresti, Fitri (Universitas Muhammadiyah Surakarta, 2021)
Purpose: This study aims to see differences in student learning performance in online learning based on gender and field of science. Methodology: The sample in this study was 488 students in Indonesia. Collection of learning performance data from student GPA. Data were analyzed using descriptive statistics and non-parametric inferential with Mann- Whitney U with SPSS 20 for windows. The Mann-Whitney U test was carried out to see differences in student learning performance based on gender and field of science. Results: The results of data analysis with the Mann-Whitney U test obtained the value of sig (0.0) <0.05 Ha1 is accepted so that it can be concluded that there is a significant difference in learning performance during the covid-19 pandemic based on the field of science. Furthermore, for differences in learning performance based on gender, the value of sig (0.039) <0.05, Ha2 is accepted so it can be concluded that there is a significant difference in learning performance during the covid-19 pandemic based on gender.